RNA editing by ADARs is important for normal behavior in Caenorhabditis elegans - Tonkin, Leath A. (Oxford University Press, 2002)
Here we take advantage of the well-characterized and simple nervous system of Caenorhabditis elegans to further our understanding of the functions of RNA editing. We describe the two C.elegans ADAR genes, adr-1 and adr-2, and characterize strains containing homozygous deletions in each, or both, of these genes. We find that adr-1 is expressed in most, if not all, cells of the C.elegans nervous system and also in the developing vulva. Using chemotaxis assays, we show that both ADARs are important for normal behavior. Biochemical, molecular and phenotypic analyses indicate that ADR-1 and ADR-2 have distinct roles in C.elegans, but sometimes act together.